The educational purposes of Physical Education - curricular dialogues between Brazil and Portugal - Tiago Nicola Lavoura; Rui Neves
Abstract Aim: The paper aims to analyse the educational purposes of Physical Education (PE) present in the national documents and programmes created in Brazil and Portugal that are geared towards its teaching in elementary schools. Methods: Since the research is of a theoretical-conceptual, documentary type character, content analysis was used to identify the category matrices of the sources analysed. Results: The results suggest approaches and specific features in skills development which are analysed and discussed based on the scientific production of the area's academic-professional field. The predominance of operational competencies is limited towards practicing PE activities, which is consistent with the pedagogical theory of competency formation. Conclusion: This concept maintains that tacit knowledge and sensory experiences are essential for performance. However, the implementation of cognitive and affective competencies are important tools for performance, particularly with adolescent students.